2016
DOI: 10.1108/jsma-01-2015-0002
|View full text |Cite
|
Sign up to set email alerts
|

Exploring connections: aspiration levels, culture and the resource based view

Abstract: Purpose – The purpose of this paper is to consider the linkages between two theories of firm performance, aspiration theory and the resource-based view (RBV), possible ways in which these theories may interact, and how the culture from which the firm originated can be a factor in how the firm may react to Schumpeterian shock issues suggested in RBV of the firm. Design/methodology/approach – This paper takes a theoretical approach. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 49 publications
0
8
0
1
Order By: Relevance
“…On this issue, Lewellyn and Bao (2015), find that outperforming industry peers and national culture are both important for explaining variance in firm-level R&D investment by shaping how performance feedback is interpreted and processed. Additionally, Chun (2016) proposes that the greater the differences in systems and hierarchies of values between cultures, the greater the differences in goals and aspiration levels between these cultures. As stipulated in Hypothesis 2a, firms engage in more ISA for negative aspiration performance but do less so for performance exceeding organizational aspirations.…”
Section: Going International: a Behavioral Perspectivementioning
confidence: 99%
“…On this issue, Lewellyn and Bao (2015), find that outperforming industry peers and national culture are both important for explaining variance in firm-level R&D investment by shaping how performance feedback is interpreted and processed. Additionally, Chun (2016) proposes that the greater the differences in systems and hierarchies of values between cultures, the greater the differences in goals and aspiration levels between these cultures. As stipulated in Hypothesis 2a, firms engage in more ISA for negative aspiration performance but do less so for performance exceeding organizational aspirations.…”
Section: Going International: a Behavioral Perspectivementioning
confidence: 99%
“…However, the result of this study is asymmetrical and relates to the previous studies from Carr and Smeltzer (2000), Schütz et al (2019), and which revealed that purchasing skills, as reflected by technical knowledge, interpersonal, and managerial skills, have significant effects on corporate performance. The different results of empirical studies may be partly due to different sample sizes, different industry types, sizes, and environments (Saldanha el al., 2019) and heterogeneous resources and capabilities, face different strengths and weaknesses leading to different performances (Chun, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Second, it is assumed that resource heterogeneity can persist over time because the resources used to implement corporate strategy are not perfect across the enterprise (some resources cannot be traded in the market and are difficult to accumulate and replicate). Chun (2016) said that the main thrust resource-based view company are heterogeneous and this heterogeneity includes the development of skills Advances in Economics, Business and Management Research,volume 40 and the ability to access and control resources. In writing the resource-based view has direct implications on the level of aspiration of the company, such company must make decisions about what resources should be spent and in what ways depending on what is considered the most important objectives of the company.…”
Section: Resource Based View Theorymentioning
confidence: 99%